Predictors of hip fracture mortality in Ghana: a single-center prospective study - Baidoo, P.K.; Odei, J.B.; Ansu, V.; Segbefia, M.; Holdbrook-Smith, H. (Archives of Osteoporosis, 2021)
Summary To determine risk factors influencing mortality in patients with proximal femur fractures in a Ghanaian hospital over a 4-year period. Methods Incidence of mortality was assessed among 76 participants with proximal femur fractures from January to December 2014 and followed up for 4 years. Outcomes of interest were mortality at 1 month, 6 months, 1 year, and 4 years. Hazard ratios (HRs) were calculated using Cox proportional hazards regression, adjusting for mortality risk factors. Results Among the 76 participants (mean age 75.8 years [SD = 12.02], 36 (47.4%) males), there were 21 death cases. The mean time of injury to surgery was 16.4 (SD = 16.2) days. Hip fractures comprised of 38 (50%) intertrochanteric, 35 (46.05%) transcervical, and 3 (3.95%) basicervical. Mortality at 1 month, 6 months, 1 year, and 4 years were 6.6%, 13.2%, 19.7%, and 27.6%, respectively. Multiple regression analysis showed a yearly increase in age that was associated with a 1.03-fold increase in the risk of death (p = 0.17). Comparing males to females, there was a significant difference in mortality (HR = 5.24, p = 0.03). Participants with basicervical hip fracture versus those with transcervical hip fracture were at higher risk of dying (HR = 28.88, p = 0.01). Patients with abnormal/low creatinine as compared to those with normal creatinine were at higher risk of dying (HR = 5.64, p = 0.005). Also, participants with an American Society of Anesthesiologists (ASA) score of III or IV were 2.73 times more likely to experience death than those with an ASA score of I or II (95% CI: 0.93–8.89, p = 0.08). Additionally, a higher risk of death was associatedwith patients with chronic obstructive pulmonary disease (COPD) (HR = 53.45, p = 0.001) and osteoporosis (HR = 8.75, p = 0.006). Conclusion Being male, having basicervical hip fracture, abnormal/low creatinine, and a history of COPD and osteoporosis were the main predictors of mortality in the study population. These findings could serve as a guide when managing patients with proximal femur fractures to improve the outcome.
Research Article
Keywords: Hip fracture; Risk factors; Mortality; Ghana